2015
DOI: 10.1016/j.addbeh.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Habit doesn't make the predictions stronger: Implicit alcohol associations and habitualness predict drinking uniquely

Abstract: Introduction As research on implicit (in the sense of fast/reflexive/impulsive) alcohol associations and alcohol advances, there is increasing emphasis on understanding the circumstances under which implicit alcohol associations predict drinking. In this study, we investigated habitualness of drinking (i.e., the extent to which drinking is automatic or occurs without thinking) as a moderator of the relations between several measures of implicit alcohol associations and key drinking outcomes. Method A sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Neither reflective drinking norms nor alcohol expectancies were assessed in this study and remain interesting potential mediators for future investigations. Additionally, following studies documenting the unique contribution of implicit alcohol associations to the prediction of college drinking (Lindgren et al, 2015; Houben & Wiers, 2008), it will be important for future research to examine implicit alcohol cognitions, in addition to explicit cognitions, as they relate to exposure to peers’ alcohol references and images on SMS.…”
Section: Discussionmentioning
confidence: 99%
“…Neither reflective drinking norms nor alcohol expectancies were assessed in this study and remain interesting potential mediators for future investigations. Additionally, following studies documenting the unique contribution of implicit alcohol associations to the prediction of college drinking (Lindgren et al, 2015; Houben & Wiers, 2008), it will be important for future research to examine implicit alcohol cognitions, in addition to explicit cognitions, as they relate to exposure to peers’ alcohol references and images on SMS.…”
Section: Discussionmentioning
confidence: 99%
“…Lindgren et al (2015) reported positive correlations between scores several scores reflecting alcohol problems and habitualness of drinking. Palfai and Ostafin (2003) also found positive correlations between scores on the approach/avoid IAT and binge drinking, difficulty to control alcohol consumption, and general sensitivity to positive incentives.…”
Section: Wanting Likingmentioning
confidence: 97%
“…Gatersleben et al (2014, Study 2) found that measures of environmental and frugal identities mediated between environmental values and pro-environmental behaviors ( β s = 0.35 and 0.28, respectively). Lindgren et al (2015) found a significant correlation between an implicit measure of drinking identity and drinking habit ( r = 0.36). Verplanken and Roy (2016) found that an index of pro-environmental habits correlated significantly with biospheric values ( r = 0.31), personal norms ( r = 0.45), and personal involvement ( r = 0.30), i.e., constructs that are closely related to self-identity.…”
Section: Introductionmentioning
confidence: 93%